2021
DOI: 10.3390/molecules26041059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Study on Fragmentation Pathways of a Novel Nerve Agent, ‘Novichok (A234)’, in Aqueous Solution by Liquid Chromatography–Tandem Mass Spectrometry

Abstract: As a first step toward studying the properties of Novichok (ethyl (1-(diethylamino)ethylidene)phosphoramidofluoridate (A234)), we investigated its degradation products and fragmentation pathways in aqueous solution at different pH levels by liquid chromatography–tandem mass spectrometry. A234 was synthesized in our laboratory and characterized by nuclear magnetic resonance spectroscopy. Three sets of aqueous samples were prepared at different pH levels. A stock solution of A234 was prepared in acetonitrile at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…In the meantime, theoretical and mass spectrometry studies have appeared that ascertain the structures shown in Fig. 1 (Bhakkoa et al 2019 ; Lee et al 2021 ; Jeong et al 2021 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the meantime, theoretical and mass spectrometry studies have appeared that ascertain the structures shown in Fig. 1 (Bhakkoa et al 2019 ; Lee et al 2021 ; Jeong et al 2021 ).…”
mentioning
confidence: 99%
“…(iv) Analytical chemistry and biomonitoring: sophisticated analytical methods, such as LC-MS/MS, must be used to analytically characterize Novichok agents (e.g., A 234). Recent progress in this direction has been reported (Lee et al 2021). Another A 234 (Cai et al 2018;Lee et al 2021).…”
mentioning
confidence: 99%
See 3 more Smart Citations